ANALISIS TINGKAT KEPUASAN KERJA KARYAWAN PEMANEN KELAPA SAWIT PT AGRO SINERGI NUSANTARA KEBUN BATEE PUTEH AFDELING 1 - irawan, rahmat feby; Handayani, Sri (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2023)
This study aims to analyze the Job Satisfaction Level of Palm Oil Harvester Employees at PT Agro Sinergi Nusantara Kebun Batee Puteh Afdeling 1, Teunom District, Aceh Jaya Regency. The sample in this study was the harvest workforce in the afdeling area I of Batee Puteh Garden which amounted to 17 employees with a total sampling technique, which is the entire population at the study site. The method used in this study is a descriptive analysis method, because the variables observed are qualitative. The data measurement technique carried out in this study is to use the Likert scale. The results showed that employee satisfaction in the Batee Puteh Afdeling 1 plantation area was included in the Satisfied category. This shows that employee job satisfaction in the Afdeling I Kebun Batee Puteh area is quite good. It can be seen based on the results of questionnaires distributed to employees. The salary of employees in the afdeling I area of Batee Puteh Gardens averages Rp.3,200.00: 26 working days = Rp.123,076 with proof that the worker has never received a permit. In the social aspect of work, 88% are included in the category of quite satisfied and 12% are categorized as satisfied.